The Performing Life: A Singer's Guide to Survival - Mabry, Sharon (Rowman & Littlefield Publishers, 2012)
The Performing Life: A Singer’s Guide to Survival is the first-hand account of the 35-year career of singer, music professor, and recording artist Sharon Mabry, who draws on personal experience to explore how professional singers survive in the face of personal and professional pressures, exorbitant expectations, illness, and the demands of their public. She details the factors that can change the course of a particular performance or an entire career. Mabry offers sage advice for how singers can bolster themselves mentally, physically, and emotionally in order to maintain their powers of performance. Divided into two parts The Performing Life focuses first on such basics as the need for extensive preparation, discovering your performance niche, acquiring mentors, determining your “maintenance level,” finding a strong support system, learning how and what to organize, and discovering how to groom body and mind. In the second half, Mabry draws on her wealth of personal stories to dig more deeply into such seemingly mundane but absolutely critical matters as personal health (illness, food allergies, insomnia), logistical challenges presented by venue location and performance dynamics, and the difficulties off-stage organized by the recording studio. In all instances, Mabry illustrates how perseverance, organization, attention to detail, excellent training, strong planning, a resilient support system, and a good sense of humor can lead to a successful and satisfying career during even the most difficult times.